An Indigenous Pacific Human Rights Mechanism: Some Building Blocks - Baird, Natalie; Toki, Valmaine (Victoria University of Wellington Law Review, 2009)
This article explores the possibility of a Pacific regional human rights mechanism, in particular in regard to how the rights contained in such a mechanism should be framed. It provides a case study of the New Zealand seabed and foreshore legislation and its impact in New Zealand as well as the CERD Committee’s reaction to the challenge to that legislation. Secondly, the article using the case study as a starting point, discusses the importance of an indigenous "lens" to develop the composition of rights in a Pacific regional mechanism.